The effect of a carbohydrate mouth rinse on neuromuscular fatigue following cycling exercise - Jeffers, R.; Shave, R.; Ross, E.; Stevenson, E. J.; Goodall, S. (Applied Physiology, Nutrition, and Metabolism, 2015)
Carbohydrate (CHO) mouth-rinsing, rather than ingestion, is known to improve performance of high-intensity (>75% maximal oxygen uptake) short-duration (=1 h) cycling exercise. Mechanisms responsible for this improvement, however, are unclear. The present study aimed to investigate the effect of a CHO mouth-rinse on cycling time-trial (TT) performance and mechanisms of fatigue. On 2 separate occasions, 9 male cyclists (mean ± SD; maximal oxygen uptake, 61 ± 5 mL/kg/min) completed 45 min at 70% maximum power output (preload) followed by a 15-min TT. At 7.5-min intervals during the preload and TT, participants were given either a tasteless 6.4% maltodextrin mouth-rinse (CHO) or water (placebo (PLA)) in a double-blind, counterbalanced fashion. Isometric knee-extension force and electromyographic responses to percutaneous electrical stimulation and transcranial magnetic stimulation were measured before, after the preload, and after the TT. There were greater decreases in maximal voluntary contraction after the TT in PLA (20% ± 10%) compared with the CHO (12% ± 8%; P = 0.019). Voluntary activation was reduced following exercise in both trials, but did not differ between conditions (PLA -10% ± 8% vs. CHO -5% ± 4%; P = 0.150). The attenuation in the manifestation of global fatigue did not translate into a TT improvement (248 ± 23 vs. 248 ± 39 W for CHO and PLA, respectively). Furthermore, no differences in heart rate or ratings of perceived exertion were found between the 2 conditions. These data suggest that CHO mouth-rinsing attenuates neuromuscular fatigue following endurance cycling. Although these changes did not translate into a performance improvement, further investigation is required into the role of CHO mouth-rinse in alleviating neuromuscular fatigue.